TOI-1468: a system of two transiting planets, a super-Earth and a mini-Neptune, on opposite sides of the radius valley - Chaturvedi, Priyanka; Bluhm, Paz; Molaverdikhani, Karan; Kossakowski, Diana; Quirrenbach, Andreas; Reffert, Sabine (Astronomy and astrophysics, 2022)
We report the discovery and characterization of two small transiting planets orbiting the bright M3.0V star TOI-1468 (LSPM J0106+1913), whose transit signals were detected in the photometric time series in three sectors of the TESS mission. We confirm the planetary nature of both of them using precise radial velocity measurements from the CARMENES and MAROON-X spectrographs, and supplement them with ground-based transit photometry. A joint analysis of all these data reveals that the shorter-period planet, TOI-1468 b (P b = 1.88 d), has a planetary mass of M b = 3.21 ± 0.24 M ⊕ and a radius of R b = R ⊕, resulting in a density of ρ b = g cm−3, which is consistent with a mostly rocky composition. For the outer planet, TOI-1468 c (P c = 15.53 d), we derive a mass of M c = M ⊕,aradius of R c = 2.06 ± 0.04 R ⊕ and a bulk density of ρ c= g cm−3, which corresponds to a rocky core composition with a H/He gas envelope. These planets are located on opposite sides of the radius valley, making our system an interesting discovery as there are only a handful of other systems with the same properties. This discovery can further help determine a more precise location of the radius valley for small planets around M dwarfs and, therefore, shed more light on planet formation and evolution scenarios.